Complementarities or Contradictions? Scoping the Health Dimensions of "Flexicurity" Labor Market Policies. (July 2013) - Afzal, Zabia; Muntaner, Carles; Chung, Haejoo; Mahmood, Qamar; Ng, Edwin; Schrecker, Ted
Flexicurity, or the integration of labor market flexibility with social security and active labor market policies, has figured prominently in economic and social policy discussions in Europe since the mid-1990s. Such policies are designed to transcend traditional labor-capital conflicts and to form a mutually supportive nexus of flexibility and security within a climate of intensified competition and rapid technological change. International bodies have marketed flexicurity as an innovative win-win strategy for employers and workers alike, commonly citing Denmark and the Netherlands as exemplars of best practice. In this article, we apply a social determinants of health framework to conduct a scoping review of the academic and gray literature to: ( a ) better understand the empirical associations between flexicurity practices and population health in Denmark and ( b ) assess the relevance and feasibility of implementing such policies to improve health and reduce health inequalities in Ontario, Canada. Based on 39 studies meeting our full inclusion criteria, preliminary findings suggest that flexicurity is limited as a potential health promotion strategy in Ontario, offers more risks to workers' health than benefits, and requires the strengthening of other social protections before it could be realistically implemented within a Canadian context.